El proceso de planeación para el desarrollo territorial “Caso municipio de Lejanías, Meta - Construcción de un modelo de desarrollo sostenible para la vigencia 2016 - 2019” (2018)
The development of research is based on the application of the principles and methodology of the BIT PASE (Balance and Interaction of Population, Environmental, Social and Economic Stress) model, which establishes the need to generate a balance between the dimensions of development and a harmonious relationship between the population and its territory. In this way the application of the model in the municipality of Lejanías allowed to strengthen the processes of governance for the construction of the public policy around the territorial development from the actors of the municipality, in which are the Communal Action Boards, associations of small producers , The Territorial Planning Council, the Municipal Development Council, the Municipal Council, the municipal administration, the National Police, among other institutions that were part of the process and allowed a solid construction of the local development plan and the mechanisms for monitoring.